2021
DOI: 10.1523/jneurosci.1022-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin 1 and ErbB4 Kinase Actively Regulate Sharp Wave Ripples in the Hippocampus

Abstract: Sharp wave ripples (SW-Rs) in the hippocampus are synchronized bursts of hippocampal pyramidal neurons (PyNs), critical for spatial working memory. However, the molecular underpinnings of SW-Rs remain poorly understood. We show that SW-Rs in hippocampal slices from both male and female mice were suppressed by neuregulin 1 (NRG1), an epidermal growth factor whose expression is enhanced by neuronal activity. Pharmacological inhibition of ErbB4, a receptor tyrosine kinase for NRG1, increases SW-R occurrence rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 104 publications
(221 reference statements)
0
5
0
Order By: Relevance
“…Additionally, the BBB is affected after BT, exposing the brain to inflammation. In adult rodents, NRG1 crossed the intact BBB activating midbrain ErbB4 receptors by phosphorylation, increasing DA levels in the substantia nigra and striatum [154,158], and exerting beneficial effects on endothelial permeability and BBB permeability after BT [159]. This evidence shows the potential of NRG as a neuroprotective factor to induce neurological recovery after brain injury.…”
Section: Btmentioning
confidence: 76%
“…Additionally, the BBB is affected after BT, exposing the brain to inflammation. In adult rodents, NRG1 crossed the intact BBB activating midbrain ErbB4 receptors by phosphorylation, increasing DA levels in the substantia nigra and striatum [154,158], and exerting beneficial effects on endothelial permeability and BBB permeability after BT [159]. This evidence shows the potential of NRG as a neuroprotective factor to induce neurological recovery after brain injury.…”
Section: Btmentioning
confidence: 76%
“…This analysis revealed that FSI in the App NL-G-F group at P60 had distinctive intrinsic properties since they clustered in a separate area of the plot compared to the App NL-G-F group at P30 and the WT groups at P30 and P60 (Fig Moreover, we found that the synaptic pathways were scarcely affected by maturation to these pathways were selected based on their involvement in gamma oscillations and FSI functionality as potential causes of early functional impairment during amyloid pathology progression. Kcnc1 [45][46][47], Kcns3 [48,49], Scn1a [50,51], Erbb4 [52][53][54][55],…”
Section: -Fast-spiking Interneuron Intrinsic Properties and Postsynap...mentioning
confidence: 99%
“…Finally, alterations in neuregulin1 (NRG1)-ErbB4 signaling have been demonstrated to alter memory performance. However, depending on the model, ablating ErbB4 in PV INs of hippocampal CA1 either enhance (Tian et al, 2017) or impair (Robinson et al, 2022) spatial and working memory performance.…”
Section: Mirna Regulation Of Gabaergic Interneuron Function In Physio...mentioning
confidence: 99%